The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/s20030713
|View full text |Cite
|
Sign up to set email alerts
|

MOM/GA-Based Virtual Array for Radar Systems

Abstract: This paper introduces a novel antenna array synthesis for radar systems based on the concept of a virtual antenna array (VAA) and the method of moments/genetic algorithm (MoM/GA) synthesis method. The VAA concept is applied to both scanning and fixed radiation pattern arrays. The proposed VAA is introduced to simultaneously support the medium-range radar (MRR) and the long-range radar (LRR) with beam width ±7° for LRR and ±37° for MRR. The proposed VAA is distinguished by its minimum number of antenna elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Planar antennas offer low cost, low weight, and very modest geometry [18][19][20]. Various simple techniques can be used to provide high gain when compared to the horn antennas commonly used in GB-SAR devices [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Planar antennas offer low cost, low weight, and very modest geometry [18][19][20]. Various simple techniques can be used to provide high gain when compared to the horn antennas commonly used in GB-SAR devices [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…There is another trend for synthesizing antenna arrays using a fewer number of elements by using virtual antenna array (VAA) beamforming. The VAA concept is widely used in antenna array-based applications such as radar systems, multiple-input multiple-output (MIMO) systems, direction of arrival (DoA) estimation, and null broadening as introduced in [8][9][10][11][12][13][14]. In [8], the VAA has been used for MIMO synthetic aperture radar (SAR).…”
Section: Introductionmentioning
confidence: 99%
“…Where, the VAA concept is applied on one-dimensional LAA for providing satisfied performance for remote sensing. While in [9], the combination of VAA and MoM/GA beamforming techniques has been introduced for the synthesis of mediumrange radar (MRR) and long-range radar (LRR) PAA systems. The VAA is applied on a two-dimensional planar antenna array (PAA) by constructing two orthogonal LAAs.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the nonuniform virtual array provided better phase tolerance compared to the uniform virtual arrays. In [ 22 ], a novel VAA synthesis technique based on the method of moments (MoM) and the genetic algorithm (GA) was introduced for the synthesis of planar antenna arrays (PAAs) in radar systems. This technique mimicked PAAs by using two orthogonal linear antenna arrays (LAAs) whose excitation coefficients were optimized to achieve a pattern highly matched to that of the desired PAA.…”
Section: Introductionmentioning
confidence: 99%